Jahn-Teller-induced femtosecond electronic depolarization dynamics of the nitrogen-vacancy defect in diamond - Ronald Ulbricht (Nature Portfolio, 2016)
Understanding ultrafast dynamics of excited states of nitrogen-vacancy helps its manipulation for technological applications. Here the authors use polarization anisotropy spectroscopy and molecular dynamics to investigate sub-picosecond dephasing dynamics, identifying the origin of orbital averaging effects.